UTILIZATION OF INTERACTIVE VIDEO TEACHING MATERIAL IN AN EFFORT TO GROW STUDENT’S SELF-REGULATED LEARNING OF CLASS VI IN ISLAMIC ELEMENTARY SCHOOL DURING THE COVID-19 PANDEMIC - Khotibul Umam; Inqidloatul Amaniyah (JIP Jurnal Ilmiah PGMI, 2021)
Teaching materials are the most important part of education when learning is especially carried out with an online system at this time. Obstruction of communication between educators and students results in education not running perfectly. Poor communication makes educators unable to convey learning material well. Besides, many students feel bored because the material presented is very monotonous. This is where the importance of educator creativity is needed. Educators must be able to make teaching materials as attractive as possible to attract students' interest in learning. Besides that, in a situation like now, it is also very important to cultivate self-regulated learning in students so that students are accustomed to learning independently. Therefore, this study was designed to find out how useful interactive video teaching materials are to foster self-regulated learning in students. This research is a qualitative descriptive study using data collection methods in the form of a questionnaire distributed to 46 students of class VI MI Al Fithrah Surabaya as the sample. This study results that the use of interactive video teaching materials during online learning is able to help foster self-regulated learning in students.